Ecological corridor design for ecoclimatic regulation: Species as eco-engineers - Lirong Wu; Matteo Convertino (Ecological Indicators)
Global eco-climatic anomalies and extremes are increasingly severe and intertwined due to the alteration of ecohydrological feedback. Ecological corridors are crucial for achieving ecoclimatic regulation goals, such as biodiversity and carbon sequestration enhancement. A key question remains about which interconnected areas to protect and restore under the set goals. This study proposes a multi-scale Ecological CORRidor design framework and model (ECORR) for ecoclimatic regulation. The South China tiger is taken as an epitome of a rare and high-dispersal species to guide ecosystem restoration via the design of ecological corridors. To construct the ecological network, we first identified the nodes as ecological source patches, which are relatively undisturbed forest areas derived from the thresholded habitat suitability (HS) using the MaxEnt model. The edges of the network were defined as least-cost pathways (LCP) using the Linkage Mapper model. For the structural evaluation, we employed key connectivity metrics such as the Integral Index of Connectivity (IIC) and delta IIC (dIIC). A restoration evaluation index (REI) was novelly introduced to compare the effect of the restoration actions. The REI consists of three parts: patch areas, change in ecosystem Forest Landscape Integrity Index (FLII), and change in species-dependent HS. The optimal Pareto solution is defined by the maximum rate of change of REI, which corresponds to the optimal trade-off between patch size and connectivity, where IIC is the ecological cost. Our results highlight that the size of ecological sources contributes predominantly to the systemic landscape connectivity due to their lower resistance to ecological flows with a minimum cost. However, corridors with high dIIC values play a vital role in connecting isolated patches, preventing fragmentation. The network-based model demonstrated in this study provides a robust framework for prioritizing restoration activities, focusing resources on patches and corridors that maximize connectivity. By leveraging rare high-dispersal species, and accounting for the ecohydrological structure of habitats and their quality, the optimal ecosystem restoration that supports global ecoclimatic regulation can be defined from coordinated bottom-up linkages.